Removal of heavy metals from acid mine drainage using chicken eggshells in column mode. (1st March 2017) - Zhang, Ting; Tu, Zhihong; Lu, Guining; Duan, Xingchun; Yi, Xiaoyun; Guo, Chuling; Dang, Zhi
Abstract: Chicken eggshells (ES) as alkaline sorbent were immobilized in a fixed bed to remove typical heavy metals from acid mine drainage (AMD). The obtained breakthrough curves showed that the breakthrough time increased with increasing bed height, but decreased with increasing flow rate and increasing particle size. The Thomas model and bed depth service time model could accurately predict the bed dynamic behavior. At a bed height of 10 cm, a flow rate of 10 mL/min, and with ES particle sizes of 0.18–0.425 mm, for a multi-component heavy metal solution containing Cd 2+, Pb 2+ and Cu 2+, the ES capacities were found to be 1.57, 146.44 and 387.51 mg/g, respectively. The acidity of AMD effluent clearly decreased. The ES fixed-bed showed the highest removal efficiency for Pb with a better adsorption potential. Because of the high concentration in AMD and high removal efficiency in ES fixed-bed of iron ions, iron floccules (Fe2 (OH)2 CO3 ) formed and obstructed the bed to develop the overall effectiveness. The removal process was dominated by precipitation under the alkaline reaction of ES, and the co-precipitation of heavy metals with iron ions. The findings of this work will aid in guiding and optimizing pilot-scale application of ES to AMD treatment. Highlights: The ES fixed bed can simultaneously and efficiently remove heavy metals and reduce the acidity of AMD. XRD and SEM–EDX analyses demonstrated the co-precipitation of heavy metals with iron ions on ES. ES fixed bed had the highest removal efficiency and adsorption potential for Pb (II). The Thomas model and BDST model could predict the performance of ES fixed bed. The findings of this work would optimize pilot-scale application of ES to AMD treatment.